Reconstruction of metatarsal bone after giant cell tumor resection with no vascularized fibular graft in a pediatric patient: Case report and review of literature - Florio, M.; Careri, S.; Zoccali, C.; Aulisa, A. G.; Falciglia, F.; Toniolo, R. M.; Giordano, M. (Frontiers in Pediatrics, 2022)
The Giant Cell tumor (GCT) is a benign, locally aggressive lesion that cause bone destruction and shows a malignant potential. It is a relatively common skeletal tumor that is therefore typically seen in young adults. Few cases are described in literature of TGC in the immature skeleton, and the metatarsal is an unusual location for a primary bone GCT, especially in pediatric age. Therefore, there are very few data reported regarding the management protocol of GCT in metatarsal bones. We report a case about the use of no vascularized fibular graft for an original Y-shaped reconstruction of the metatarsal bone after Giant Cell Tumor resection in a 9 years-old patient, and performed a literature review about metatarsal bone reconstruction in skeletally immature patient.